The suitability of outing frequency as a definition of hikikomori (prolonged social withdrawal) - Nonaka, Shunsuke; Sakai, Motohiro (Frontiers in Psychiatry, 2023)
Recent research has employed outing frequency, referred to in this study as one’s frequency of going out of the home, as a condition to define and determine the severity of hikikomori (prolonged social withdrawal). However, there is little definitive evidence on this topic. Furthermore, compared to the previous definition, it is unclear how the scope of hikikomori included in the proposed condition differs. This study aimed to clarify the relationship between hikikomori tendencies and the frequency and quality of outings to bridge this gap in research. Methods Data included 397 self-rated online samples, 72 self-rated offline samples, and 784 parent-rated samples. Quantitative and qualitative indicators of outings and subjective social functioning impairment were used in the analysis. Results The cut-off points supported the criteria for the number of days outside the home proposed in previous studies. The results revealed that the outing frequency condition excluded about 14.5–20.6% of those previously considered to have hikikomori. Logistic regression analysis showed that low outings with interpersonal interaction, low frequency of outings, and high subjective social functioning impairment consistently predicted hikikomori. However, outings without interpersonal interaction did not predict hikikomori. Conclusion These results indicate that outing frequency tends to be suitable as one of the conditions for hikikomori. However, they indicate that we should also focus on the quality of outings, that is, outings with or without interpersonal interaction, to evaluate hikikomori consistently with previous findings. Further research is needed to clarify the appropriate frequency of outings to define hikikomori and determine its severity.